(3JTQjYGJ eGdjI heUQajIs - (3QTGO(B, (3GdYUGQs ((3YeGf(B:s (3OGQ GdHQcI ddfTQ hGdJhRjY(B,s, 2001)
(3GdLhGfH GdbGfhfjI ddCYeGd GdHfhc GdJLGQjI hChLg GdQbGHI Ydi fTGWgG(B- (3GdLhGfH GdbGfhfjI ddCYeGd GdHfc GdeQcRj(B- (3GdJfXje GdbGfhfj ddCYeGd GdeDSSGJ GdeGdjI GdeJNUUI(B- (3GdLhGfH GdbGfhfjI ddhOGFY GdeUQajI(B- (3GdLhGfH GdbGfhfjI ddMSGH GdLGQj(B- (3GdLhGfH GdbGfhfjI ddEYJeGO GdeSJfOj(B- (3GdLhGfH GdbGfhfjI dNWGH GdVeGf(B- (3GdLhGfH GdbGfhfjI ddGYeGd GdUQGaI(B- (3GdLhGfH GdbGfhfjI dYedGJ GdCLfHjI(B- (3GdLhGfH GdbGfhfjI ddESJKeGQ hJTLjYg(B.s
Keywords: (3GdJTQjYGJ GdeUQajIs; (3GdbGfhf GdeGdjs